Planifier le désordre, se préparer à l’imprévisible - Gérard Dubey (Revue d'anthropologie des connaissances)
The operating room, because the body is opened there, exerts on ordinary mortals a power of attraction in which fascination and repulsion mix. Few workspaces can boast such an aura. In anthropology, the techniques implemented by surgeons are most often related to symbolic practices (propitiatory rites) intended to protect the “officiants” from the proximity of a danger which is none other than the secularized figure of the sacred. But in surgery the symbolic function is never unrelated to experiential knowledge acquired over a long period of time. The article reports on this action planning work upstream of the OR intervention. It draws on the first results of an empirical investigation begun two years ago within the framework of the innovation chair of the APHP-BOPA (Augmented Operating Room at CHB Brousse-Villejuif). The main hypothesis discussed in this article is the structuring dimension of uncertainty in preoperative activity.